Rare cause of gastric outlet obstruction - Sonal Gandhi; Niraj Jani (Greater Baltimore Medical Center, 2018)
Bouveret's syndrome is a rare cause of gastric outlet obstruction. The stones enter the small bowel via cholecysto-enteric fistula. The most common presenting symptoms are abdominal pain, nausea and vomiting. The gold standard diagnostic test isesophagogastroduodenoscopy (EGD). Rigler's triad on abdominal x-ray is classic. CT scan findings are pneumobilia, cholecystoduodenal fistula and a gallstone in the duodenum. We present a case of a 75-year-old female who presents with 3 week history of nausea, vomiting, and diffuse abdominal pain. Initial presentation, imaging and EGD was concerning for malignancy. She was later diagnosed to have Bouveret's syndrome and underwent laparoscopic small bowel enterotomy with removal of gallstones